THE INFLUENCE OF SERVICE QUALITY AND PRICES ON PURCHASING DECISIONS AT WARUNG ANGKRINGAN (Case study of boarding house residents in Yogyakarta) - In Lia Amalia Qori, Hurin; Asyriana Br.P, Sofia (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This study aims to find out whether service quality and price influence consumer decisions about their purchases at angkringan stalls (a case study of boarding houses in the city of Yogyakarta). The population of this study was all residents living in boarding houses in Yogyakarta, especially students/workers. The sample is 140 respondents with a purposive sampling technique. The questionnaire was prepared according to the Likert scale. The analytical method used was multiple linear regression analysis. The results of the correlation regression analysis obtained the equation: Y = 0,852 + 0,429 X1 + 0,268 X2 + e This proves that there is a positive influence from the variables of Service Quality and Price on Consumer Decisions of angkringan stalls in Yogyakarta.Keywords: service quality; price; purchase decision